2015
DOI: 10.5897/ajar2014.9263
|View full text |Cite
|
Sign up to set email alerts
|

Post-harvest effects on beverage quality and physiological performance of coffee beans

Abstract: During coffee drying, different temperatures applied to the beans with varied humidity content levels can interfere in the membranes integrity, germination, organic acid and carbohydrate content resulting in coffees with distinct flavors. The quality control of the beans will be much more effective the earlier the alterations provoked in the postharvest are detected. This work has an objective to study alternative methods for the dehydration of the coffee beans using ultra-drying followed by slow drying and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 29 publications
1
34
0
9
Order By: Relevance
“…On the other hand, Taveira et al. () documented the same results, elaborating that average sun‐drying rates on drying patios (temperature: 10 to 28 °C and RH: 34.5% to 61.2%) are 0.002 kg/kg H 2 O/hr for fully washed coffee and 0.002 kg/kg H 2 O/hr for natural coffee. In agreement with the results of Tsegaye, Mohammed, Shimber, Getachew, and Getachew (), Taveira and colleagues also claimed better cup quality conservation for slow drying (60/40 °C, details below) on patios with hot air rather than on flat‐ground surfaces.…”
Section: Postharvest Processing Systemsmentioning
confidence: 71%
“…On the other hand, Taveira et al. () documented the same results, elaborating that average sun‐drying rates on drying patios (temperature: 10 to 28 °C and RH: 34.5% to 61.2%) are 0.002 kg/kg H 2 O/hr for fully washed coffee and 0.002 kg/kg H 2 O/hr for natural coffee. In agreement with the results of Tsegaye, Mohammed, Shimber, Getachew, and Getachew (), Taveira and colleagues also claimed better cup quality conservation for slow drying (60/40 °C, details below) on patios with hot air rather than on flat‐ground surfaces.…”
Section: Postharvest Processing Systemsmentioning
confidence: 71%
“…The type of coffee processing methods (wet and dry) that are performed to obtain the green beans determined the flavour properties and created a typical quality difference [3,19]. Several reports also stated the final cup quality and chemical composition are also defined by the adopted method in wet processing [20][21][22]. The effect of different modified wet-processing methods on the final quality of coffee is evaluated and compared by Gonzalez-Rios et al [21].…”
Section: Wet Processingmentioning
confidence: 99%
“…The coffee beans that are obtained using dry-processing method are usually called unwashed (natural) coffee. In this processing method, to get the green coffee beans, the harvested cherry is dried in the sun or other mechanical drier and followed by separating the dried outer parts [22]. Sun drying is a lengthy process, and 95% of Arabica coffee from Brazil, Ethiopia, Haiti, Indonesia, Paraguay, India, and Ecuador are sun-dried [42].…”
Section: Dry Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent results have shown that changes that occur in coffee seeds during the postharvest operations influence the chemical composition and integrity of enzyme systems, affecting its physiological quality (Bytof et al, 2007;Saath et al, 2014;Taveira et al, 2015). Therefore, the aim of this study was to determine endo-β-mannanase enzyme activity on dry and soaked coffee seeds, evaluating the relationship between this activity and the effects of processing and drying of seeds in physiological quality.…”
Section: Introductionmentioning
confidence: 99%